AAC services in schools: a special educator's perspective. (15th March 2019) - Andzik, Natalie R.; Chung, Yun-Ching; Doneski-Nicol, Janis; Dollarhide, Colette T.
Abstract : Objectives: Students with intellectual and developmental disabilities often require augmentative and alternative communication (AAC) to fully meet their academic and social potential. AAC supports can be challenging for some educators to implement. This study sought to bring light to these challenges. Methods: A qualitative interview approach was utilized to examine the perspectives of 14 special education teachers who supported students using AAC systems. Participants described their experiences regarding providing AAC services. Results: Despite receiving some supports, the majority of teachers identified challenges, including inadequate training, lack of comprehensive assessment, inadequate preparation time, and inconsistent AAC implementation across team members. Conclusion: This study highlighted key factors that impacted AAC access and outcomes of students with complex communication needs. Practical implications and future research needed to enhance the communication outcomes of students were discussed.